Eternal - Scottoline, Lisa (New York : Random House Large Print, 2021)
Elisabetta, Marco, and Sandro grow up as the best of friends despite their differences. Elisabetta is a feisty beauty who dreams of becoming a novelist; Marco the brash and athletic son in a family of professional cyclists; and Sandro a Jewish mathematics prodigy, kind-hearted and thoughtful, the son of a lawyer and a doctor. Their friendship blossoms to love, with both Sandro and Marco hoping to win Elisabetta's heart. But in the autumn of 1937, all of that begins to change as Mussolini asserts his power, aligning Italy's Fascists with Hitler's Nazis and altering the very laws that govern Rome.
Keywords: World War, 1939-1945 -- Fiction; Jews -- Fiction; Survival -- Fiction; Triangles (Interpersonal relations) -- Fiction; Large type books; Rome -- Fiction; Historical fiction